Balancing viral replication in spleen and liver determines the outcome of systemic virus infection - Lang, K. S.; Lang, P. A. (Zeitschrift für Gastroenterologie, 2015)
The innate immune system limits virus replication during systemic infection by producing type I interferons (IFN-I) but still has to allow viral replication to achieve maximal innate and adaptive immune activation. Some spleen and lymph node resident antigen presenting cells (APCs) show limited response to IFN-I due to expression of the endogenous inhibitor of IFN-I signaling, Usp18. Therefore, virus in this spleen niche replicates despite high levels of IFN-I. This enforced viral replication leads to an exorbitant propagation of viral antigens and viral RNA. Viral antigen leads to massive activation of the adaptive immune system, while viral RNA to activated innate immunity. In contrast to these APCs, liver resident Kupffer cells, take up most of the systemic virus and suppress its replication in response to IFN-I. In addition, virus specific CD8 + T cells which are primed in the spleen migrate to the liver and kill virus infected cells. In this review we discuss the different mechanisms, which influence immune activation in spleen and antiviral mechanisms in the liver and how they determine the outcome of virus infection.
Keywords: Hepatitis C; Virushepatitis; Leber; Immunaktivierung; Hepatitis B